Ensaios sobre as feiras orgânicas e agroecológicas em Fortaleza, Ceará: redes sociais e práticas de gerenciamento - Vilhena, Luciana Girão de (2024)
In view of global changes regarding eating habits, an improved social awareness emerges, aimed at quality of life, opening space for the flourishing of a new market: the production, commercialization and consumption of organic food. Based on this theme and paying attention to the economic importance of this market, this thesis presents three essays that look at organic products, the organization of holidays that sell this type of product, as well as the level of business management of farmers. The first aimed to carry out a content review on the topic of organic products in the Brazilian context between 2010 and 2021 from the perspective of lexical analysis. Then, with a quantitative and qualitative approach, the content of the selected articles was analyzed using the IRAMUTEq software. The results lead us to deduce the incipience of work related to organic products with family farming, rural development, public policies and organic/agroecological fairs. The second essay aimed to analyze the network of organic and agroecological products in organic and agroecological open-air markets in Fortaleza from the perspective of access and exchange of information between network agents. The research was carried out in the municipality of Fortaleza at five local fairs, the most relevant being: a) Gentilândia fair; b) Adahil Barreira Park fair; c) Rio Mar Kennedy Shopping fair; d) Mercado dos Pinhões fair; and e) fair at the Frei Humberto Training and Qualification CenterThe main finding was the low interaction network between the groups of stallholders, however, the potential to increase their interactions and communications was revealed. The results show that the networks are recent and, for this reason, some producers maintain strong and positive interactions with other producers. The third essay analyzes the business management practices employed by producers/vendors of organic and agroecological products in the five main fairs in the city of Fortaleza during the year 2023. The methodology involves multifaceted analyzes of the interactions between management variables and the measurement of the Relative Business Management Index (IRGE) of producers and sellers of organic/agroecological products through exploratory factor analysis and cluster analysis. The results showed that 60% of producers/traders adopt more than 75% of management practices, even if in an incipient way. Furthermore, it was observed that two clusters of producers have a low level of management, one of which is made up of members with low education and the other is made up, essentially, of women.